Implementasi Pendidikan Seks terhadap Perilaku Anak dalam Bergabung dengan Sesama Berbasis Video Animasi: Implementation Of Sex Education On Children's Behavior In Associating With Peers Based On Animation Videos - Nurhusni Kamil; Fadila Arnisa Harahap; Lilia Nurramadani; Yuanita Anthon Sope (Universitas Ngudi Waluyo, 2024)
It is necessary to introduce the concept of sex education to children from an early age because this is the basis for children interacting with peers. Sex education in society is usually a taboo subject, but actually it is no longer taboo and needs to be introduced clearly. There are many methods that parents can use. In this study, researchers implemented an introduction to the concept of sex education to children through animated video services. This is because children tend to like things that move and make sounds, such as films or videos, compared to just visualization shows such as story books. This type of research uses qualitative research with a case study approach. The case study is a model that focuses on exploring